Disuse as a problem of defining grammatical categories - Sargsyan, Artashes (Bulletin of Yerevan University B: Philology, 2022)
In different grammatical systems there may be word forms that are not used or are used very rarely, but their composition does not contradict the general system. Such unused or rarely used grammatical forms may be in noun, pronoun, and verb systems and refer to their different grammatical orders. The question arises whether such forms should be considered non-existent, or their possible use should not be ruled out. This problem is especially relevant when compiling grammatical dictionaries, in which all grammatical forms of a word should be presented. The article deals with issues related to this issue.
Keywords: grammatical form; conjugation system; singular; plural; infinitive; verb; irregular verb; noun; pronoun; grammar dictionary